Primeval and other times - Tokarczuk, Olga; Lloyd-Jones, Antonia (Prague, Czech Republic : Twisted Spoon Press, 2010)
Set in the mythical village of Primeval, a microcosm of the world populated by eccentric, archetypal characters and guarded by four archangels, the novel chronicles the lives of the village's inhabitants over the course of the feral 20th century and the episodice violence visited on them.
Translation of: Prawiek i inne czasy.
Keywords: City and town life -- Poland -- Fiction; Polish literature -- 20th century